Determinants of unfavorable prognosis for out-of-hospital sudden cardiac arrest in Bielsko-Biala district - Gach, Dariusz; Nowak, Jolanta U.; Krzych, Łukasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction: The prognosis in out-of-hospital sudden cardiac arrest (OHCA) remains unfavorable and depends on a number of demographic and clinical variables, the reversibility of its causes and its mechanisms. Aim: To investigate the risk factors of prehospital death in patients with OHCA in Bielsko County. Material and methods: The study analyzed all dispatch cards of the National Emergency Medical Services (EMS) teams in Bielsko-Biala for the year 2013 (n = 23 400). Only the cards related to sudden cardiac arrest in adults were ultimately included in the study (n = 272; 190 men, 82 women; median age: 71 years). Results : Sixty-seven victims (45 men, 22 women) were pronounced dead upon the arrival of the EMS team, and cardiopulmonary resuscitation (CPR) was not undertaken. In the remaining group of 205 subjects, CPR was commenced but was ineffective in 141 patients (97 male, 44 female). Although univariate analysis indicated 6 predictors of prehospital death, including OHCA without the presence of witnesses (odds ratio (OR) = 4.2), OHCA occurring in a public place (OR = 3.1), no bystander CPR (OR = 9.7), no bystander cardiac massage (OR = 13.1), initial diagnosis of non-shockable cardiac rhythm (OR = 7.0), and the amount of drugs used for CPR (OR = 0.4), logistic regression confirmed that only the lack of bystander cardiac massage (OR = 6.5) and non-shockable rhythm (OR = 4.6) were independent determinants of prehospital death (area under ROC curve = 0.801). Conclusions : Non-shockable rhythm of cardiac arrest and lack of bystander cardiac massage are independent determinants of prehospital death in Bielsko-Biala inhabitants suffering from OHCA.